TEORI DAN PENDEKATAN YANG MENDASARI IMPLEMENTASI PEMBELAJARAN MENULIS - Herman Budiyono (Jurnal Ilmiah Universitas Batanghari Jambi, 2011)
For the implementation of learning to write effectively and efficiently implemented, learning to write should be based on the theories and approaches accordingly. This paper describes the underlying theory and approach to the implementation of learning to write. For that, there are two main things described in this paper, namely (1) theory of language learning and the process of writing and (2) approach to learning to write. The first description includes a theory of language learning (Behavioristic, mentalistik, andBialystok) and the writing process (prapenulisan, writing drafts, and revisions). The description covers both communicative and integrative approach.